Dengue virus and Japanese encephalitis virus infection of the central nervous system share similar profiles of cytokine accumulation in cerebrospinal fluid - Haipeng Li; Yuanyuan Li; Bo Wen; Jian Zhang; Chengwu Wang; Zhanyi Song; Shuochi Li; Xiaowang Qu; Renbin Huang; Wenpei Liu (Central European Journal of Immunology)
Dengue virus (DENV) and Japanese encephalitis virus (JEV) are two important pathogenic viruses that can cause severe encephalitis, which is accompanied by inflammatory cytokines. However, the inflammatory cytokine content of cerebrospinal fluid (CSF) in DENV and JEV infection of central nervous system are not sufficiently studied. To investigate cytokine levels in serum and CSF of hospitalised children with DENV and JEV infection of the central nervous system, a total of 183 hospitalised children with viral encephalitis-like syndrome were enrolled between May 2014 and April 2015 at the Children’s Hospital of Chenzhou, Hunan, China. DENV and JEV infection was diagnosed by ELISA. Cytokine levels in the serum and CSF were measured by commercial ELISA kits. Twenty-nine (15.85%) and 26 (14.21%) DENV and JEV infections were detected in 183 patients with viral encephalitis-like syndrome, respectively. Higher granulocyte-macrophage colony-stimulating factor (GM-CSF) levels were detected in the serum of JEV infected patients than in DNEV patients (p < 0.05) or in healthy controls (p < 0.001), and levels of GM-CSF, interleukin 6 (IL-6) and monocyte chemoattractant protein-1 (MCP-1) were higher in the CSF than serum in both DENV and JEV infection. Both DENV and JEV infection induced similar cytokine accumulation profiles in the CSF, which probably contributed to DENV- and JEV-induced immunopathogenesis.